Effects of Livable Housing on Community Quality of Life: A Macro-Micro Study - Widy Atmojokusumo; Christina Ruth Elisabeth (Jurnal Permukiman, 2026)
Starting from the issue that access to adequate housing had only reached 38.3% by the year 2019, as evaluated through four basic parameters in the Sustainable Development Goals (SDGs). This study investigates the extent to which the livable housing indicators in SDGs influence the overall quality of life. The quality of life is assessed at the macro level using the Human Development Index parameters and at the micro level through the outcomes of government assistance programs. The results of multiple linear regression indicate that most livable housing parameters exert a strong, significant influence on the community's quality of life at the macro level. Meanwhile, the micro-community’s perception in the research sample confirms Bappenas’s findings and the SDGs. Considering that all parameters of livable houses significantly influence quality of life at the macro level, the research sample unit at the micro level has provided adequate confidence in most aspects of livable housing. Through this study, the authors expect that the Government can maximize the program's effectiveness in expanding household access to adequate housing, thereby achieving the target of at least 74% accessibility by 2029.